Training on writing children's stories with religious moderation insight for children's story writers in Jakarta - Dwi Puji Lestari; Rika Febrianti (Universitas Muhammadiyah Magelang, 2023)
The purpose of this activity is to provide an understanding of the insight into the values of religious moderation in stories to writers of children's stories. The method used for this activity is Participatory Action Research (PAR) which goes through the introduction stage, setting goals and objectives, determining children's story training and evaluating the assessment of children's story products with an insight into religious moderation. The results of this activity show that the training participants can understand religious moderation as evidenced by the increased post-test results, participants can present religious moderation material in written stories and participants can produce children's stories with an insight into religious moderation.